2016
DOI: 10.1038/srep27489
|View full text |Cite
|
Sign up to set email alerts
|

Novel TetR family transcriptional factor regulates expression of multiple transport-related genes and affects rifampicin resistance in Mycobacterium smegmatis

Abstract: Transport-related genes significantly affect bacterial antibiotic resistance. However, the effects of these genes and their regulation of bacterial drug resistance in several mycobacterial species, including the fast-growing Mycobacterium smegmatis, the pathogen M. tuberculosis and M. avium have not been clearly characterized. We identified Ms4022 (MSMEG_4022) as a novel TetR family regulator that activates the expression of seven transport-related genes and affects drug resistance in M. smegmatis. Overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Also, of the 4 proteins identified as down regulated (absent in treated samples) in time point three, two are predicted transporters of the major facilitator superfamily. A recent study identified Ms4022 (MSMEG_4022) as a novel TetR-family regulator that directly activates the expression of seven transport related genes and enhanced M. smegmatis resistance to anti-tuberculosis drugs including rifampicin 34 . In the current study however Ms4022 did not significantly differ between treatment and control groups across all three time points (see Supplementary Spreadsheet S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, of the 4 proteins identified as down regulated (absent in treated samples) in time point three, two are predicted transporters of the major facilitator superfamily. A recent study identified Ms4022 (MSMEG_4022) as a novel TetR-family regulator that directly activates the expression of seven transport related genes and enhanced M. smegmatis resistance to anti-tuberculosis drugs including rifampicin 34 . In the current study however Ms4022 did not significantly differ between treatment and control groups across all three time points (see Supplementary Spreadsheet S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other TFTRs are activators [7] and some can act as both activators and repressors [8]. TFTRs have been identified which can bind multiple targets [9, 10] and intergenic regions [11]. Thus, although some TFTRs are known to be local repressors, the current classification system is, in some cases, oversimplifying these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of the introduction of foreign DNA into M. smegmatis in 1987, M. smegmatis has been used as the workhorse of mycobacterial research and as a surrogate model for pathogenic and slower‐growing mycobacterial species such as M. leprae and M. tuberculosis (Liu, Yang, & He, ; Titgemeyer et al., ). In this study, M. smegmatis was utilized as a surrogate host for M. tuberculosis to further investigate the roles of DdlA in mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Fumonisin, a notorious mycotoxin, consists of aminopolyols with a core structure containing a 19-or 20-carbon backbone with methyl, hydroxyl, and tricarballylic acid moieties at different sites along the carbon backbone (Baird et al, 2008). Currently, accumulating evidence shows that fumonisin, which is a polyketide derivative and is structurally related to sphinganine, usually causes a variety of toxicological effects, such as esophageal cancer, cardiovascular problems, and neural tube defects, in humans and animals (Desjardins, Munkvold, Plattner, & Proctor, 2002;Waskiewicz, Stepien, Wilman, & Kachlicki, 2013 (Liu, Yang, & He, 2016;Titgemeyer et al, 2007). In this study, into anti-TB drug design to combat the difficult-to-treat pathogen M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%